(untitled) (The Journal of Interdisciplinary Human Studies, 2025)
This study examines the historiography of the Bukhara Emirate by analyzing the works of local, Soviet-era, and foreign researchers. As one of the key political and cultural centers of Central Asia from 1756 to 1920, the Bukhara Emirate has attracted the attention of numerous scholars. The research highlights the diversity of historical approaches and the significance of manuscript sources, diplomatic reports, and archival materials in reconstructing the emirate’s political, social, and cultural life. Special attention is given to the contributions of foreign travelers and orientalists, who documented the administrative structure, religious hierarchy, and daily life of the region. The analysis also emphasizes the need for further objective and comprehensive studies, particularly in the context of Uzbekistan’s independence, which has opened new opportunities for unbiased historical inquiry. Overall, the study demonstrates the continuing relevance of the Bukhara Emirate’s history for modern scholarship.